Defense Industry Management In Defense Equipment Procurement Offset Contracts To Improve The Defense Economy - Muhammad Renditya; Suwito Suwito; Heru Prasetyo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This research aims to contribute ideas to policy makers in managing the defense industry, especially through offset contracts for defense equipment procurement. Using a descriptive-qualitative analysis method, data is collected from secondary and primary sources, then analyzed qualitatively to draw conclusions regarding the management of the defense industry to improve the defense economy. The results show that the implementation of offset contracts requires a large initial investment and often exceeds the available budget, and faces the challenge of a technology gap between Indonesia's defense industry and developed countries. Sustainability of offset programs requires long-term maintenance of investments and technological capabilities. Case studies in Turkey, India, Brazil and France show success in increasing local defense industry capacity and reducing import dependency. In Indonesia, cooperation with France in MEF phase II 2015-2019 was effective in meeting TNI's defense equipment needs and technology transfer, although improvements in the sea and air defense sectors are still needed. With the right incentives, strategic partner selection, and human resource enhancement, the local defense industry can develop and reduce the technology gap.